Future teachers’ mathematics cognitive failures and their learning styles - Adeneye Olarewaju Awofala; Ruth Folake Lawal; Abayomi Adelaja Arigbabu (Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
This study investigated the disparities in the mathematics cognitive failures of future mathematics teachers based on learning style inclination. As a descriptive survey study, the sample included 480 future mathematics teachers from four universities in south-west Nigeria. Two research questions were involved and two instruments were used for the collection of quantitative data for the study: Learning Style Inventory (LSI, Cronbach alpha coefficient=0.74) and the Mathematics Cognitive Failures Questionnaire (MCFQ, Cronbach alpha coefficient=0.89). The collected data were analyzed using one-way Analysis of Variance (ANOVA), frequency, and percentage. Results showed that future mathematics teachers in varying degrees preferred the four learning styles of convergers, divergers, accommodators, and assimilators. In addition, there was a statistically significant influence of learning style on future teachers’ mathematics cognitive failures. Thus, there were meaningful disparities in mathematics cognitive failures between accommodators and the other three types of future teachers: divergers, convergers, and assimilators. The disparity was in support of the accommodators. Succinctly, the accommodators pooled the greatest mathematics cognitive failures while the divergers recorded the least mathematics cognitive failures. In line with these study findings, it is advised that strategies that could reduce future teachers’ mathematics cognitive failures and close the gaps created by learning styles should be enacted to promote their success in mathematics learning.